Simulation of climatic effects on temperature-controlled containerized cargo - Sergio Barbarino; Oliver Klein; Rainer Müller; Cory Rosa; Philippe Sibomana; Nils Meyer-Larsen; Alex Wunsch (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
This paper describes the so-called CORE Simulation Environment (CORE-SE), a scenario based simulation environment which was developed in the scope of the EU project CORE. CORE-SE in particular provides means for the simulation of logistics scenarios. It consists of a software agent platform that facilitates a multiagent-based simulation (MABS) approach. In MABS, the environment and the objects acting therein are modelled by a number of software agents. CORE-SE provides a platform to create and configure different simulation scenarios and finally 'run' them by the emulation of the agents' behaviours in a coordinated and controlled way. CORE-SE, as described in this paper, has been applied in a specific supply chain sce-nario related to product integrity due to cargo temperature requirements where higher temperature (and solar radiation) could result in fluctuating product integrity in terms of quality loss and damage. During the simulated transport, climatic and weather-related factors like ambient temperature, ground temperature, solar radiation, and wind speed together with the resulting effects on the inner container temperature are simulated and respectively calculated according to the actual transport route of the container by usage of a climatic data model. The paper presents first results of the analysis, which are used to optimize the temperature control of the cargo, thereby better taking into account the mentioned external factors.
urn:nbn:de:gbv:830-88217702; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; Containerized cargo; Container; Clima; Climatic effects